Ethics-Based Information Security System Law: Immanuel Kant's Transcendental Paradigm - Jaya, Indra; Septyanun, Nurjannah; Erwin, Yulias (Universitas Muhammadiyah Surakarta, 2024)
An ethics-based information security system based on Immanuel Kant's transcendental legal paradigm can give a strong foundation for tackling moral quandaries in AI, hacking, and information systems. Lavanya Singh highlights the necessity of instinctive ethics based on philosophical literature and presents a Kantian ethics application that adheres to the philosophical tradition. Meanwhile, Sanchita Saha et al. address ethical hacking as a method of disclosing vulnerabilities in information systems for the benefit of society, emphasizing ethical concerns in cybersecurity operations. Furthermore, Flávia Maria Santoro and Rosa Maria Esteves Moreira da Costa underline the significance of examining information systems via an ethical lens in order to negotiate conceptual conflicts and make informed judgments in delicate situations, which is consistent with Kant's moral philosophy. Using doctrinal research methodologies with legal material sources derived from literature studies and qualitative descriptive analysis. This study discovered that by incorporating Kant's concepts into information security systems, the transcendental legal paradigm may guide ethical decision making and promote responsible technological advancement. The Ethics-Based Information Security Systems Act, modeled after Immanuel Kant's Transcendental Paradigm, would prioritize universal ethical principles, respect for human autonomy, duty-bound behaviors, transparency, accountability, and a structured regulatory framework. The law will guarantee that information security is maintained not just through technological means, but also via a solid ethical foundation that respects the dignity and rights of all those concerned.